2021
DOI: 10.3390/ma14061398
|View full text |Cite
|
Sign up to set email alerts
|

Water-Tree Resistant Characteristics of Crosslinker-Modified-SiO2/XLPE Nanocomposites

Abstract: Trimethylolpropane triacrylate (TMPTA) as a photoactive crosslinker is grafted onto hydrophobic nanosilica surface through click chemical reactions of mercapto double bonds to prepare the functionalized nanoparticles (TMPTA-s-SiO2), which are used to develop TMPTA-s-SiO2/XLPE nanocomposites with improvements in mechanical strength and electrical resistance. The expedited aging experiments of water-tree growth are performed with a water-knife electrode and analyzed in consistence with the mechanical performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Other interfacial chemistries in Figure S3a (Supporting Information), such as thiol/double bond click reaction and thiol/epoxy click reaction, have been well characterized, which are helpful for improving the interfacial adhesion. [31,32] Also, in addition to silane treatment of substrate, we also provided three surface modification methods including surface primer, polydopamine (PDA)-coating, and surface initiation to expand the universality of the strategy (Figure S3b, Supporting Information). Taking PDMS as an example, the surface primer method can cure the PDMS precursor with active functional groups (such as amino group, sulfhydryl group, and double bond) on the substrate in situ to obtain the surface with active functional groups.…”
Section: Materials Characterizationmentioning
confidence: 99%
“…Other interfacial chemistries in Figure S3a (Supporting Information), such as thiol/double bond click reaction and thiol/epoxy click reaction, have been well characterized, which are helpful for improving the interfacial adhesion. [31,32] Also, in addition to silane treatment of substrate, we also provided three surface modification methods including surface primer, polydopamine (PDA)-coating, and surface initiation to expand the universality of the strategy (Figure S3b, Supporting Information). Taking PDMS as an example, the surface primer method can cure the PDMS precursor with active functional groups (such as amino group, sulfhydryl group, and double bond) on the substrate in situ to obtain the surface with active functional groups.…”
Section: Materials Characterizationmentioning
confidence: 99%
“…Usually, water trees do not cause an insulation breakdown, but these can create PD or electrical trees, which are recognized as the primary factors contributing to insulation failure . To overcome this problem, researchers tried to improve the manufacturing technology by adding water tree retardant material and developing semiconducting materials with higher purity. These methods helped by delaying the formation of electrical trees but could not eliminate the whole problem. Later, it was found that not only the traces of water trees can initiate the formation of electrical trees but the presence of protrusion or roughness of the surface of the insulating polymers can also initiate the formation of electrical trees. Moreover, at the interphase of different materials during the manufacturing of power cables, the formation of voids or cavities cannot be entirely avoided.…”
Section: Introductionmentioning
confidence: 99%
“… 7 To overcome this problem, researchers tried to improve the manufacturing technology by adding water tree retardant material and developing semiconducting materials with higher purity. 8 10 These methods helped by delaying the formation of electrical trees but could not eliminate the whole problem. Later, it was found that not only the traces of water trees can initiate the formation of electrical trees but the presence of protrusion or roughness of the surface of the insulating polymers can also initiate the formation of electrical trees.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is necessary to use coupling agents to organically modify the surface of the nano-zeolite and improve its dispersion performance in the polyethylene matrix. At the same time, other functional groups, such as groups improving thermal conductivity or auxiliary crosslinking agents, can be introduced by grafting to make the nano-zeolite more evenly dispersed and fixed in the XLPE crosslinking network [12][13][14].…”
Section: Introductionmentioning
confidence: 99%